Normative misperceptions of tobacco use among university students in seven European countries: Baseline findings of the 'Social Norms Intervention for the prevention of Polydrug usE' study. (December 2015) - Pischke, Claudia R.; Helmer, Stefanie M.; McAlaney, John; Bewick, Bridgette M.; Vriesacker, Bart; Van Hal, Guido; Mikolajczyk, Rafael T.; Akvardar, Yildiz; Guillen-Grima, Francisco; Salonna, Ferdinand; Orosova, Olga; Dohrmann, Solveig; et al.
Abstract: Introduction: Research conducted in North America suggests that students tend to overestimate tobacco use among their peers. This perceived norm may impact personal tobacco use. It remains unclear how these perceptions influence tobacco use among European students. The two aims were to investigate possible self-other discrepancies regarding personal use and attitudes towards use and to evaluate if perceptions of peer use and peer approval of use are associated with personal use and approval of tobacco use. Methods: The EU-funded 'Social Norms Intervention for the prevention of Polydrug usE' study was conducted in Belgium, Denmark, Germany, Slovak Republic, Spain, Turkey and United Kingdom. In total, 4482 students (71% female) answered an online survey including questions on personal and perceived tobacco use and personal and perceived attitudes towards tobacco use. Results: Across all countries, the majority of students perceived tobacco use of their peers to be higher than their own use. The perception that the majority (> 50%) of peers used tobacco regularly in the past two months was significantly associated with higher odds for personal regular use (OR: 2.66, 95% CI: 1.90–3.73). The perception that the majority of peers approve of tobacco use was significantly associated with higher odds for personal approval of tobacco use (OR: 6.49, 95% CI: 4.54–9.28). Conclusions: Perceived norms are an important predictor of personal tobacco use and attitudes towards use. Interventions addressing perceived norms may be a viable method to change attitudes and tobacco use among European students, and may be a component of future tobacco control policy. Highlights: Tobacco use remains substantial among European university students. Students appear to have misperceptions of peer use and approval of tobacco use. Perceived norms are an important predictor of personal tobacco use.